New Insights on the Pathogenesis of Takayasu Arteritis: Revisiting the Microbial Theory - Espinoza, J. Luis (Pathogens, 2018)
Takayasu arteritis (TAK) is a chronic vasculitis that mainly affects the aorta, its major branches, and the pulmonary arteries. Since the description of the first case by Mikito Takayasu in 1908, several aspects of this rare disease, including the epidemiology, diagnosis, and the appropriate clinical assessment, have been substantially defined. Nevertheless, while it is well-known that TAK is associated with a profound inflammatory process, possibly rooted to an autoimmune disorder, its precise etiology has remained largely unknown. Efforts to identify the antigen(s) that trigger autoimmunity in this disease have been unsuccessful, however, it is likely that viruses or bacteria, by a molecular mimicry mechanism, initiate or propagate the auto-immune process in this disease. In this article, we summarize recent advances in the understanding of TAK, with emphasis on new insights related to the pathogenesis of this entity that may contribute to the design of novel therapeutic approaches.